Novel study on investigating the mechanical, microstructure morphological, and dry sliding wear characteristics of grey cast iron GG25 with copper additions for valve guides in internal combustion engine - Singh, Baljeet; Singh Grewal, Jasmaninder; Kumar, Rajeev; Sharma, Shubham; Kumar, Abhinav; Mohammed, Kahtan A.; Awwad, Fuad A.; Khan, M. Ijaz; Ismail, Emad A. A. (Frontiers in Materials, 2024)
The valve guide is an essential part of valve train assembly and affects the engine performance. Due to long term operation, it is preferred to be made of cast iron owing to its good casting and machining ability. Therefore, the dry sliding behavior of cast iron GG25 with copper additions has been investigated. Wear characteristics have been studied by varying loads at 30N, 40N and 50 N keeping velocity constant i.e., 1 m/s and varying sliding velocities at 0.5, 1, and 2 m/s keeping load constant i.e., 30N at room temperature. It has been reported that, when the normal load is increased from 30 N to 40 N, the wear losses rise from 222 to 417 microns, which is double the wear loss at moderate speeds (133 to 222 microns at 0.5m/s to 1m/s). The highest wear loss at higher sliding speeds of 2m/s, however, was 1226 microns as opposed to 617 microns at higher normal loads of 50 N. In conclusion, normal load is more significant up to moderate loading and speed circumstances, and sliding speed is more significant at higher sliding speeds, leading to increased wear losses. Frictional forces and coefficient of friction have also been measured. It is concluded that friction coefficient rises from 0.238 to 0.436 at 30N to 50N loading situations and at different speeds it remains fairly constant. The wear mechanisms of worn-out samples have been studied using scanning electron microscope coupled with EDX. It has been concluded that the increased sliding speed exhibited significant implications on the wear losses as compared to the increased loading conditions.